Cardiac phenotype in propionic acidemia: results of an observational monocentric study - Kovacevic, Alexander; Garbade, Sven; Hoffmann, Georg F.; Gorenflo, Matthias; Kölker, Stefan; Staufner, Christian (Molecular genetics and metabolism, 2020)
Background: Propionic acidemia (PA) is an organic aciduria caused by inherited deficiency of propionyl-CoA carboxylase. Left ventricular dysfunction and QT prolongation may lead to life-threatening complications. Systematic analyses of cardiac phenotypes, in particular effects of specific cardiac therapies, are scarce. Methods: In this longitudinal observational monocentric study (data from 1989 to 2017) all PA patients treated at our center were included. Echocardiographic parameters (left ventricular end-diastolic diameter: LVEDD, left ventricular shortening fraction, mitral valve Doppler inflow pattern) and 12-lead electrocardiogram recordings (corrected QT interval: QTc) were analyzed. Symptomatic patients were dichotomized to the group "early-onset" (symptoms within 28 days of life) and "late-onset" (symptoms after 28 days). Associations between cardiac function, LVEDD, QTc and clinical parameters (age at onset, beta-blocker or Angiotensin-converting enzyme inhibitor = ACE-I therapy) were analyzed. Results: 18 patients with PA were enrolled, 17 of them were symptomatic and one asymptomatic, with a median age at diagnosis of 6 days. 14/17 (82%) had early onset disease manifestation. Systolic left ventricular dysfunction (i.e. hypokinetic phenotype of cardiomyopathy) was diagnosed in 7/18 (39%) patients at a median age of 14.4 years, all had early onset. Two patients had a dilated left ventricle and systolic left ventricular dysfunction (i.e. dilated hypokinetic phenotype - dilated cardiomyopathy). Diastolic left ventricular dysfunction was found in 11/18 (61%) individuals, typically preceding systolic left ventricular dysfunction. ACE-I therapy did not improve systolic left ventricular function. Mean QTc was 445 ms (+/- 18.11 ms). Longer QTc was associated with larger LVEDD. Conclusions: Systolic left ventricular dysfunction was found in 39% of patients, reflecting high disease severity. Two thirds of all individuals showed signs of diastolic left ventricular dysfunction usually preceding systolic left ventricular dysfunction; it therefore may be considered as an indicator for early cardiac disease manifestation, possibly allowing earlier treatment modification. Unresponsiveness to routine cardiac therapy highlights the need to evaluate further strategies, such as liver transplantation.
Gesehen am 11.05.2020